2017
DOI: 10.1155/2017/9732136
|View full text |Cite
|
Sign up to set email alerts
|

Histological Evidence of the Osseointegration of Fractured Direct Metal Laser Sintering Implants Retrieved after 5 Years of Function

Abstract: Background. Direct metal laser sintering (DMLS) is an additive manufacturing technique that allows the fabrication of dental implants layer by layer through the laser fusion of titanium microparticles. The surface of DMLS implants is characterized by a high open porosity with interconnected pores of different sizes; therefore, it has the potential to enhance and accelerate bone healing. To date, however, there are no histologic/histomorphometric studies in the literature evaluating the interface between bone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 28 publications
0
20
0
5
Order By: Relevance
“…Nano-pore structure can increase the bone binding force by 3.1-fold, 17 which can imitate the cellular environment in vivo, favoring the absorption of extracellular matrix protein and promoting receptor recognition and subsequent adhesion and proliferation of cells, as well as advancing the biological behavior of cell attachment and migration through signaling of surface integrins. 16,18 In this study the rotating torsion test and histomorphometric results indicated that the SLA-Bio group had considerably greater torque strength, a larger area of bone-implant contact, and faster initiation of osseointegration in comparison with the other 2 groups. The increased osseointegration in the SLA-Bio group at early stages of healing can be achieved by the biological effects of the nano-and micro-surface structure, as well as the promotion of cellular adhesion and protein (eg, sialoprotein and osteopontin) deposition on the titanium implant surface.…”
Section: E9mentioning
confidence: 54%
“…Nano-pore structure can increase the bone binding force by 3.1-fold, 17 which can imitate the cellular environment in vivo, favoring the absorption of extracellular matrix protein and promoting receptor recognition and subsequent adhesion and proliferation of cells, as well as advancing the biological behavior of cell attachment and migration through signaling of surface integrins. 16,18 In this study the rotating torsion test and histomorphometric results indicated that the SLA-Bio group had considerably greater torque strength, a larger area of bone-implant contact, and faster initiation of osseointegration in comparison with the other 2 groups. The increased osseointegration in the SLA-Bio group at early stages of healing can be achieved by the biological effects of the nano-and micro-surface structure, as well as the promotion of cellular adhesion and protein (eg, sialoprotein and osteopontin) deposition on the titanium implant surface.…”
Section: E9mentioning
confidence: 54%
“…[53][54][55] AM technologies have been selected to manufacture Ti implants, customized subperiosteal Ti implants, [82][83][84][85][86] customized AM Ti meshes for bone grafting techniques, [87][88][89][90][91][92][93][94][95] Co-Co frameworks for implant impression procedures, 96,97 and Co-Cr and Ti implant frameworks for implant-supported prostheses. [98][99][100][101][102] With the introduction of AM technologies, different studies have analyzed the potential to manufacture Ti AM dental implants (Table 1), [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] customized designs that replicate the tooth's root shape (Table 2), [74][75]…”
Section: Application Of Am Technologies In Implant Dentistrymentioning
confidence: 99%
“…Furthermore, the mechanical properties, osteoconduction, and bone augmentation properties of titanium porous lattice structures have been evaluated. 102,103 Different in vitro and animal studies, 17,53,54,56,[60][61][62]64,72 as well as clinical studies 57,60,[65][66][67][68][69][70][71] have analyzed the utility of AM titanium implants. Authors concluded that AM technologies are an alternative for manufacturing custom implants, providing adequate and controlled porosity levels, superficial roughness that promotes new bone formation, and improves the osseointegration process.…”
Section: Application Of Am Technologies In Implant Dentistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The size of the necks is influenced by the sintering temperature and duration 61 . This large porosity translates to a large surface area, promoting better osseointegration 62 and allowing for drug delivery in joint replacements. Sintering is best performed with metals that are of a similar melting point.…”
Section: Materials Usedmentioning
confidence: 99%